The Logistics Financier as a Strategic Orchestrator: Simulating Supply Chain Finance to Unlock Profitability in State-Owned Logistics - Ria, Poeti; Rahadi, Raden Aswin (Journal Integration of Management Studies, 2026)
As the logistics industry undergoes rapid transformation, companies are evolving beyond their traditional role of transporting goods to become orchestrators of capital and information flows. While Supply Chain Finance (SCF) is widely recognized for optimizing working capital, its application in state-owned enterprises (SOEs) remains underexplored, particularly due to regulatory restrictions prohibiting direct lending. Addressing this gap, this study proposes an adaptation of the Logistics Financier orchestration model tailored for an Indonesian state-owned logistics enterprise currently experiencing a liquidity shortfall of IDR 4.3 billion. Employing an exploratory sequential mixed-method design, this research integrates expert interviews to construct model parameters and utilizes Monte Carlo simulation to assess financial robustness. The simulation reveals that a holistic SCF approach—integrating Purchase Order (PO) Financing and Reverse Factoring—can effectively bridge a funding gap of IDR 39 billion and generate an expected net profit of IDR 12.8 billion. However, a critical finding indicates negative profitability (-1.62%) within the Government segment, highlighting a theoretical misalignment between market-driven SCF tools and bureaucratic governance structures. This study contributes to SCF literature by conceptualizing the orchestrator’s role as a financial intermediary and empirically demonstrating that SCF serves as a high-sensitivity value amplifier. Its effectiveness depends on institutional context and strict operational discipline.